Medical Inpatients’ Perceptions of Patient-centred Care and its Effect on Quality Nursing Care and Patient Satisfaction: A Qualitative Study in Northern Ghana - Abugre, D.; Bhengu, B. R. (British Journal of Healthcare and Medical Research, 2022)
Background: Efforts by many researchers for a universal definition of the concept of patient-centred care (PCC) appears elusive and makes its implementation problematic. The missing link to PCC implementation in nursing care is the need for nurses to understand patients’ perspective, apply PCC principles and good relational and communication skills to develop individualised patient care plans. Methods: A qualitative study that explored perceptions of patient-centred care and its effects on nursing care quality and patient satisfaction among medical inpatients at discharge. Results: Three themes emerged from the study including the meaning of PCC, PCC practices, and the effect of PCC on nursing care with nine subthemes identified. The meaning of PCC was varied with four subthemes such as nurses performing core nursing care with professionalism, good interpersonal and communication skills, involving patients and relatives in the care process, and respecting patients’ cultural values and spiritual beliefs. The inpatients desired that nurses pray with them and provide a place for patients to pray in the wards. PCC practices included practices the inpatients observed or received. Positive perception of PCC positively affected the perception of quality of nursing care, patient satisfaction, and health status. Poor nurse attitude and inadequate interpersonal and communication skills negatively affected the perception of PCC. Conclusion: The inpatients had a clear understanding of PCC and nurses need to incorporate patients’ perceptions and involve patients and relatives in nursing care. Holistic nursing care including attending to spiritual needs, good interpersonal and communication skills are essential for effective implementation of PCC.